ChemInform Abstract: Shape‐Controlled Metal Nanocrystals for Catalytic Applications. Issue 1 (January 2015) - Ruditskiy, Aleksey; Choi, Sang‐Il; Peng, Hsin‐Chieh; Xia, Younan
Abstract Review: 55 refs.